Is it possible to identify infrahissian cardiac conduction abnormalities in myotonic dystrophy by non-invasive methods?. Issue 5 (1st November 1999) - Babuty, D; Fauchier, L; Tena-Carbi, D; Poret, P; Leche, J; Raynaud, M; Fauchier, J P; Cosnay, P
Abstract : OBJECTIVE: To identify intracardiac conduction abnormalities in patients with myotonic dystrophy from their clinical, ECG, and genetic features. METHODS: 39 consecutive patients (mean (SD) age 42.9 (12.1) years; 16 female, 23 male) underwent clinical examination, genetic studies, resting and 24 hour ambulatory ECG, signal averaged ECG, and electrophysiological studies. RESULTS: 23 patients suffered from cardiac symptoms, 23 had one or more cardiac conduction abnormality on resting ECG, one had sinus deficiency, and 21 (53.8%) had prolonged HV intervals. No correlation was found between the severity of the neurological symptoms, onset of disease, cardiac conduction abnormalities on ECG, and the intracardiac conduction abnormalities on electrophysiological study. The size of the DNA mutation was longer in the abnormal HV interval group than in the normal HV interval group (3.5 (1.8) v 2.2 (1.0) kb, p < 0.02). Signal averaged ECG parameters (total QRS duration (QRSD) and duration of low amplitude signals ⩽ 40 μV (LAS 40)) were greater in patients with an abnormal HV interval than in those with a normal HV interval (123.4 (24.6) v 102.8 (12.3) ms and 47.5 (12.8) v 35.3 (8.8) ms, respectively; p < 0.005). Only the association of QRSD ⩾ 100 ms with LAS 40 ⩾ 36 ms identified patients with an abnormal HV interval with good sensitivity (80%) and specificity (83.3%). CONCLUSIONS: Infrahissian conduction abnormalities are common in myotonic dystrophy and can be identified using signal averaged electrocardiography.